Library Resources and Services Satisfaction for Users: A Case Study of IIT Libraries in India: Enhancing User Satisfaction with Library Resources and Services: A Case Study of IIT Libraries in India (Journal of Advances and Scholarly Researches in Allied Education, 2015)
This study examines user satisfaction with the library resources and services available in IIT libraries in India. To define the research issues, a survey research method was adopted. In order to gather relevant information on their satisfaction, 900 questionnaires were distributed to final year students, graduation students, research scientists and faculty members from IIT libraries. There were received and analyzed 758 completed questionnaires. On this basis, a few suggestions to increase user satisfaction from libraries have been included in this research.